ENSURING EQUITY IN AN UNEQUAL WORLD: FRAMEWORK FOR AN ALTERNATE DEVELOPMENT PARADIGM - Sandhya S. Iyer; K. Seeta Prabhu (Revista Tempo do Mundo)
The objective of the study is to analyze the multifaceted crises affecting global development, such as the Covid-19 pandemic, climate change, and increasing inequality. It critiques the traditional gross domestic product (GDP) driven development model and suggests an alternative framework based on the principles of equity and sustainability. This approach aligns with the Lifestyle for Environment (LiFE) initiative and seeks to integrate human development with ecological sustainability. The research emphasizes the importance of global leadership, particularly through the Group of Twenty (G20), in fostering international cooperation to facilitate a just transition through policy reforms and behavioral changes.